Social, Personal, and Innovative Competencies Effect of Service-Learning in Physical Education Teacher Education: A Mixed-Methods Analysis - Capella-Peris, Carlos; Martí-Puig, Manuel; Salvador-García, Celina; Maravé-Vivas, María (Frontiers in Education, 2021)
The purpose of this study was to compare the development of social entrepreneurship competency in physical education teacher education students (n=89), through two modalities of intervention from the same service-learning program. The student teachers provided a direct service to children with motor functional diversity, promoting their motor skills and counteracting their lack of social attention. The study was conducted using mixed methods with methodological triangulation. Quantitative evidence was gathered through a quasi-experimental design of two non-equivalent experimental groups implementing the Social Entrepreneurship Competency Scale. Qualitative analysis was undertaken by elaborating 12 life histories of multiple crossed stories. Quantitative results provide significant evidence about the social entrepreneurship competency effect of service-learning on physical education teacher education students while qualitative interpretation complements this view, reflecting how this competency was developed. We provide original findings on promotion of personal, social, and innovative SEC features as well as the promotion of moral and civic values.